The synthesis of copper-modified biochar from Elsholtzia Harchowensis and its electrochemical activity towards the reduction of carbon dioxide - Chen, Shiqi; Liu, Wei; Mei, Ziwei; Li, Haifu; Zhao, Wenyu; Zhao, Junkai; Tao, Hong (Frontiers in Chemistry, 2023)
Phytoremediation techniques have been widely used in the treatment of heavy metal contaminated soils in recent years, but there is no effective post-treatment method for plant tissues containing heavy metals after remediation. Elsholtzia Harchowensis is a copper hyperaccumulator, commonly distributed in copper mining areas and often used for soil remediation of mine tailings. Moreover, copper-based catalysts are widely used in electrocatalytic reduction of carbon dioxide, which aims to convert carbon dioxide into useful fuels or chemicals. In this study, copper-modified biochar was prepared from Elsholtzia Harchowensis. Its specific surface area can reach as high as 1202.9m 2 /g, with a certain porous structure and even distribution of copper on the amorphous carbon. Various products (such as carbon monoxide, methane, ethanol, and formic acid) could be obtained from the electrolytic reduction of carbon dioxide by using the as-prepared catalyst. Instantaneous current density of up to 15.3 mA/cm 2 were achieved in 1.0 M KHCO3 solution at a potential of -0.82 V (vs. RHE). Electrolysis at a potential of -0.32 V (vs. RHE) for 8 h resulted in a stable current of about 0.25 mA/cm 2 , and the Faraday efficiency (FE) of carbon monoxide can reach as high as 74.6 %. In addition, electrolysis at a potential of -0.52 V (vs. RHE) for 8 h led to a stable current of about 2.2 mA/cm 2 and a FE of 8.7% for the C2 product. The rich variety of elements in plants leads to catalysts with complex structural and elemental characteristics as well, which facilitates the electrolytic reduction of carbon dioxide with a variety of useful products.